Effectiveness of Nitrate and Beta-Blocker Drugs in Patients with Angina Pectoris: A Systematic Literature Review - Maya Arfania; Adinda Khoirun Nissa; Khoirul Haniatin; Andriyani, Novita (Eureka Herba Indonesia, 2023)
Angina pectoris is the most common clinical manifestation of myocardial ischemia and often occurs when the heart needs more blood. The main goals of treatment in patients with unstable angina are relief of symptoms, slowing disease progression, and reducing future events, especially myocardial infarction, and death. This study aimed to explore the literature regarding the effectiveness of nitrate and beta-blocker drugs in angina pectoris patients. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding risk factors and clinical overview of acute kidney injury. The search was performed using the terms: (1) "nitric oxide" OR "beta-blockers" OR "morbidity" OR "mortality" AND (2) "angina pectoris". The literature is limited to clinical studies and published in English. Sublingual nitroglycerin has become the mainstay of treatment for angina pectoris. This drug can be used to relieve acute angina or as a prophylaxis, namely before activities that can trigger angina. Beta-blockers are a type of drug that can be used to relieve angina symptoms and prevent ischemic events through the mechanism of reducing myocardial oxygen demand, reducing heart rate, and myocardial contractility. These drugs work by competitively inhibiting the action of circulating catecholamines at cell membrane beta-adrenergic receptors. In conclusion, nitrate and beta-blocker drugs are the main choices in relieving angina pectoris symptoms.